Tren Produk Blind Box: Inovasi Model Bisnis Atau Tantangan Kepatuhan Syariah? - Delia Zara Zaneta; Jhonson Jhonson; Mukhtaruddin Mukhtaruddin (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2026)
The rapidly growing trend of blind box products in digital commerce raises a fundamentalquestion regarding its position in Islamic economic law, whether it represents a legitimatebusiness model innovation or contains serious challenges to Sharia compliance. This productpotentially contains elements of gharar due to the uncertainty of the contract object at the timeof transaction. This study aims to analyze the trend of blind box products from the perspectiveof sale and purchase contracts in Islamic economic law through a literature review of nationaland international journals. The findings indicate that blind box products contain elements ofgharar fahisy due to uncertainty regarding the type, quality, and specifications of goods, therebyfailing to meet the valid requirements of sale and purchase contracts in Islam. Therefore, stricteroversight is needed to ensure this practice aligns with the principles of clarity, justice, andtransparency in Islamic economics.